Effects of gender and age on dimensions of media literacy among children - Mohd Nasir, Nur Shakira; Wok, Saodah; Mohamed, Shafizan; Wan Mohd Ghazali, Wan Norshira (2021)
This paper aims at exploring the possible effects of gender and age on dimensions of media literacy translated in terms of skills. The five dimensions of digital media literacy are: (a) informational and operational skills, (b) safety and security skills, (c) communication and participation skills, (d) content creation and innovation skills, and (e) problem solving skills. As such, this paper tries to find out the differences within gender and within age besides the interaction effect of gender and age on the aforementioned skills. A digital competence theory is used as the guide for the study. A total of 308 children who participated were obtained through telephone interviews and captured in the Google Form developed based on the questionnaire. The children were sampled from those living in the three identified Pusat Perumahan Rakyat (PPR). Results show that there is a significant difference between male and female on only problem solving skills of the digital media literacy. However, there are differences between the age groups for all the dimensions of digital media literacy where the oldest group performed better than the middle group and the youngest group. With the help of the General Linear Model Analysis, the main and the interaction effects were performed simultaneously. But, there is no interaction effect for all the dimensions of digital media literacy. Hence, the digital competence theory is partially supported. Suggestions for future research are put forth.